National, regional, and global cardiomyopathy burden from 1990 to 2019 - Cheng, Siyuan; Han, Yuchen; Jiang, Lie; Lan, Ziyin; Guo, Jun (Frontiers in Cardiovascular Medicine, 2022)
Objective: To examine the incidence of cardiomyopathy including both alcoholic cardiomyopathy (AC) and other cardiomyopathy (OC) in 204 nations and regions over the 1990 – 2019 period. Methods: The Bayesian mixed-effects DisMod-MR 2.1 meta-regression tool, which was designed to analyze GBD data, was used to estimate the prevalence of OC and AC. The GBD data are subdivided into 21 global regions based on characteristics such as geographical proximity and epidemiological similarity. The overall burden of cardiomyopathy was assessed by combining AC- and OC-related data, 95% confidence intervals were calculated based on standardized error values determined based upon the width of the 95% UI divided by 1.96×2. RESULTS: In total, the respective numbers of global deaths attributed to AC and OC were 0.07 million (95%UI: 0.06 - 0.08) and 0.24 million (95%UI: 0.19 - 0.26). The age-standardized mortality rate for cardiomyopathy in 2019 was 3.97 (95%CI: 3.29 – 4.39), with respective mortality rates of 0.86 (95%UI: 0.72 – 0.99) and 3.11 (95%UI: 2.57 - 3.4) for AC and OC. At the global level in 2019, 2.44 million (95%UI: 2.04-2.78) DALYs were attributed to AC, while 5.72 million (95%UI: 4.89-6.33) DALYs were attributed to OC. From 1990 – 2019, cardiomyopathy age-standardized prevalence rates declined by -0.49% (95%CI: -0.57 to -0.41) CONCLUSION: Previous studies have estimated the risk factors that influence the burden of multiple cardiovascular diseases (CVD).. Otherwise, this study mainly focused on cardiomyopathy, and analyzed multiple indicators from national, regional, and age-standard dimensions to identify potential risk factors including prevalence, deaths, years lived with Disability-adjusted life years (DALYs) that influence the development of AC and OC. To our knowledge, this study is the first to have systematically assessed the burden of AC and OC as of 2019 at the national, regional, and global levels and calculated DALYs to achieve a better evaluation of disease risk and quality of life of the population. The number of cases, deaths and DALYs of cardiomyopathy showed an overall increasing trend and obvious geographical differences in the past three decades.